Histopatologi Limpa dan Limfonodus pada Kasus Lapangan dengan Dugaan Kematian Akibat Virus African Swine Fever Pada Babi di Kabupaten Kupang - Gelolodo, Maria Aega; Sanam, Maxs U. E.; Toha, Larry R. W.; Widi, Antin Y. N.; Simarmata, Yohanes T. R. M. R.; Murni, Theresia F. I. M. D. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2021)
African swine fever is a fatal hemorrhagic disease in the Suidae family that has become a significant economic challenge to the global pig farming industry. The continued spread of this disease has threatened global pork production and food security. Recognizing the disease manifestations and pathological changes of ASF is critical for a comprehensive and accurate early warning program. Knowledge of the key characteristics of this disease, such as its pathology anatomy, and histopathology, is also needed for early identification of ASF before establishing a tentative diagnosis. This article aims to discuss the pathologic changes and to update disease understanding in order to improve early detection of ASF in the field. A histopathological study of clinical samples collected during the February to April 2021 outbreak of ASF was performed to determine the characteristic lesions of ASF. Three dead ASFV-suspected pigs from a farm in Kupang regency were examined in this study. The main characteristics at the gross pathology inspection were hemorrhage and enlargement of the spleens and lymph nodes. The histopathologic findings confirmed spleen and lymph nodes hemorrhages, as well as congestion of spleen and follicle necrotic at the lymph nodes. Based on the clinical manifestation, pathological findings, and epidemiology observation, it is suspected that the pigs were infected with ASF. However, a molecular diagnostic test should be taken to confirm the definitive cause of the pig’s deaths.